Endoscopic internal drainage as first-line treatment for fistula following gastrointestinal surgery: a case series - Donatelli, Gianfranco; Dumont, Jean-Loup; Cereatti, Fabrizio; Dhumane, Parag; Tuszynski, Thierry; Vergeau, Bertrand Marie; Meduri, Bruno (Endoscopy International Open, 2016)
Background and study aims: Leaks following gastrointestinal surgery are a dreadful complication burdened by high morbidity and not irrelevant mortality.Endoscopic internal drainage (EID) has showed optimal results in the treatment of leaks following bariatric surgery. We report our experience with EID as first-line treatment for fistulas following surgery along all gastrointestinal tract.